2019
DOI: 10.1136/bmjopen-2019-031550
|View full text |Cite
|
Sign up to set email alerts
|

Gout and the risk of advanced chronic kidney disease in the UK health system: a national cohort study

Abstract: ObjectiveEvaluate the association between gout and risk of advanced chronic kidney disease (CKD).DesignRetrospective matched cohort study.SettingUK Clinical Practice Research Datalink.ParticipantsThe analysis included data for 68 897 patients with gout and 554 964 matched patients without gout. Patients were aged ≥18 years, registered at UK practices, had ≥12 months of clinical data and had data linked with Hospital Episode Statistics. Patients were excluded for history of advanced CKD, juvenile gout, cancer, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 44 publications
2
22
0
3
Order By: Relevance
“…In addition, the research of Arbol et al and also Baghel et al showed that CKD was most commonly caused by DM glomerulonephritis, but Arbol et al found that the second most common cause was hypertension [9,10]. Stack et al showed that patients with hyperuricemia had a 29% higher risk of suffering from advanced CKD than patients without gout (HR, 1.29, 95% CI 1.23-1.35) [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the research of Arbol et al and also Baghel et al showed that CKD was most commonly caused by DM glomerulonephritis, but Arbol et al found that the second most common cause was hypertension [9,10]. Stack et al showed that patients with hyperuricemia had a 29% higher risk of suffering from advanced CKD than patients without gout (HR, 1.29, 95% CI 1.23-1.35) [4].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the most common risk factors for CKD are diabetes mellitus, hypertension, and other causes such as glomerulonephritis, polycystic kidney disease, kidney vascular disorders, chronic urinary tract obstruction, vesicoureteral reflux, and recurrent pyelonephritis [1]. However, at this time many new risk factors have also been investigated, such as elevated uric acid and gout [4].…”
Section: Introductionmentioning
confidence: 99%
“…The need to effectively manage gout is increasingly recognized as important because (1) gout is prevalent, and increasingly so, despite the proven effectiveness of urate-lowering therapies (ULT) such as allopurinol 2,3,4 ; (2) the effect on individuals, their families, and society has been significantly underappreciated 5,6 ; and (3) the documented poor adherence to ULT (< 50%) 7 has been moderately resistant to a wide range of interventions 8,9,10,11 . Further, there is increasing concern that poorly controlled gout is a harbinger of premature and serious cardiovascular and/or renal impairments 9,12 .…”
Section: Predictors Of Success In Gout Treatmentmentioning
confidence: 99%
“…According to a study examining the association between serum uric acid levels and kidney disease in Korean men, elevated serum uric acid levels were independently associated with an increased likelihood of CKD 16 . In addition, a recent study examining the association between gout and the risk of advanced CKD found that patients with gout had a higher incidence of advanced CKD than those without 17 .…”
Section: Introductionmentioning
confidence: 99%